An enhanced method to determine the Young's modulus of technical single fibres by means of high resolution digital image correlation. (7th March 2018) - Huether, Jonas; Rupp, Peter; Kohlschreiber, Ina; Weidenmann, Kay André
Abstract: To obtain mechanical tensile properties of materials it is customary to equip the specimen directly with a device to measure strain and Young's modulus correctly and only within the measuring length defined by the standards. Whereas a variety of tools such as extensometers, strain gauges and optical systems are available for specimens on coupon level, no market-ready tools to measure strains of single fibres during single fibre tensile tests are available. Although there is a standard for single fibre testing, the procedures described there are only capable of measuring strains of the whole testing setup rather than the strain of the fibre. Without a direct strain measurement on the specimen, the compliance of the test rig itself influences the determination of the Young's modulus. This work aims to fill this gap by establishing an enhanced method to measure strains directly on the tested fibre and thus provide accurate values for Young's modulus. It is demonstrated that by applying and then optically tracking fluorescing polymeric beads on single glass fibres, Young's modulus is determined directly and with high repeatability, without a need to measure at different measuring lengths or compensating for the system compliance. Employing this method to glass fibres, a Young's modulus of approximately 82.5 GPa was determined, which is in the range of values obtained by applying a conventional procedure. This enhanced measuring technology achieves high accuracy and repeatability while reducing scatter of the data. It was demonstrated that the fluorescing beads do not affect the fibre properties.